Cultural Constructions of the Life Cycle: An Ethnographic Study of Life Stages in Yogyakarta, Indonesia - Novita Wahyuningsih; Joko Lulut Amboro (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
Understanding the life cycle is an important aspect of cultural studies, as it contains the values, norms, and collective identity of the community that are passed down from generation to generation. This research examines the human life cycle in the cultural perspective of the people of Gunungkidul, Yogyakarta through an ethnographic approach. The life cycle starts from birth, childhood and adolescence, adulthood and marriage, to old age and death. This cycle is understood as a series of rites that are full of symbolic, spiritual and social meanings. Various traditions such as mitoni, puputan, nyanggar, circumcision, and death slametan reflect the way people celebrate and interpret life culturally. The approach used in this research is qualitative with ethnographic methods. The data collection technique in this research is triangulated through three main methods that complement each other, namely participatory observation, semi-structured in-depth interviews, and documentation studies. This research found that tradition not only functions as a celebration of biological transition, but also as a mechanism for value inheritance, identity formation, and strengthening social solidarity. Despite the pressures of globalisation and modernisation, the people of Gunungkidul show efforts to preserve traditions through cultural adaptation and revitalisation, including in local education. By placing nature and community as cultural learning spaces, the cycle of life becomes a mirror of the dynamic interaction between humans, traditions and local values. This study confirms that ethnography shows that culture in the human life cycle in the Gunung Kidul region is the main instrument in shaping human character and maintaining the continuity of the community's collective identity.